Child and adolescent mental health in primary health care - Assessment and referral (Portuguese Journal of Family Medicine and General Practice, 2009)
Child and adolescent mental health in primary health care - evaluation and referral Mental health problems in children and adolescents have been increasing over the past decades and can be considered one of the major challenges in Public Health nowadays. Child and Adolescent Mental Health Services are endowed with very scarce human resources and the search for other answers to the problem, namely in the frame of Primary Health Care, is considered urgent. It is important to enhance integrated partnership work, more solid and efficient, in order to attend these situations. Primary Health Care professionals have to attend frequently young people with mental health problems and their training needs in this specific area are becoming more pressing. In this article, the author addresses issues such as child and adolescent mental health evaluation and referral. Items and attitudes to adopt in clinical interview with parents, in child and adolescent evaluation, and in parent-child interaction observation are discussed. Also the distinction between normal and pathology and the signs for referral to the specialised services in different age groups are presented.
Keywords: Child; Adolescent; Mental Health; Primary Health Care; Diagnostic Evaluation; Referral